Rancang Bangun Sistem Informasi Penerimaan Karyawan Berbasis Web Menggunakan Metode Waterfall - Noer Hikmah; Rifqi Bagus Pratama; Suryanto Suryanto (JURIKOM (Jurnal Riset Komputer), 2018)
The employee recruitment and employee selection process is the first process for a company to get quality employees needed by the company. The need for quality human resources is an absolute need for companies to be able to develop and advance in the future. The company must first ensure the criteria for the desired employee. CV Bina Sarana Utama Cirebon often faces problems about unprofessional and qualified employees at work. This makes the company also often holds an employee recruitment process. For this reason, the authors intend to create an employee acceptance website to help CV develop the main means of Cirebon to select qualified and professional employees to join CV. The main means of Cirebon are using the Waterfall method.